Cover Image, Volume 75, Issue 10. Issue 10 (3rd December 2018) - Werner, Michael; del Castillo, Urko; Ventrella, Rosa; Brotslaw, Eva; Mitchell, Brian
Abstract : The back‐cover image is based on the Short Report The small molecule AMBMP disrupts microtubule growth, ciliogenesis, cell polarity and cell migration by M.E. Werner et al., DOI: 10.1002/cm.21507 .